Total numbers and in-hospital mortality of patients with myocardial infarction in Germany during the FIFA soccer world cup 2014 - Keller, Karsten; Hobohm, Lukas; Schmitt, Volker H.; Engelhardt, Martin; Wenzel, Philip; Post, Felix; Münzel, Thomas; Gori, Tommaso; Friedmann-Bette, Birgit (Scientific reports, 2021)
Environmental stress like important soccer events can induce excitation, stress and anger. We aimed to investigate (i) whether the FIFA soccer world cup (WC) 2014 and (ii) whether the soccer games of the German national team had an impact on total numbers and in-hospital mortality of patients with myocardial infarction (MI) in Germany. We analyzed data of MI inpatients of the German nationwide inpatient sample (2013-2015). Patients admitted due to MI during FIFA WC 2014 (12th June-13th July2014) were compared to those during the same period 2013 and 2015 (12th June-13th July). Total number of MI patients was higher during WC 2014 than in the comparison-period 2013 (18,479 vs.18,089, P < 0.001) and 2015 (18,479 vs.17,794, P < 0.001). WC was independently associated with higher MI numbers (2014 vs. 2013: OR 1.04 [95% CI 1.01-1.07]; 2014 vs. 2015: OR 1.07 [95% CI 1.04-1.10], P < 0.001). Patient characteristics and in-hospital mortality rate (8.3% vs. 8.3% vs. 8.4%) were similar during periods. In-hospital mortality rate was not affected by games of the German national team (8.9% vs. 8.1%, P = 0.110). However, we observed an increase regarding in-hospital mortality from 7.9 to 9.3% before to 12.0% at final-match-day. Number of hospital admissions due to MI in Germany was 3.7% higher during WC 2014 than during the same 31-day period 2015. While in-hospital mortality was not affected by the WC, the in-hospital mortality was highest at WC final.
Gesehen am 11.08.2021